Practical robot design : game playing robots - Kanniah, Jagannathan (Boca Raton : Taylor & Francis, 2014)
'This book presents the latest theoretical and practical developments in the field of robotics. Each chapter covers basic theory and key topics, including actuators, sensors, and microcontrollers, followed by specific robot-building applications, such as robot swarms, legged robots, underwater robots, and flying robots. The text also discusses the application of AI techniques in robotics and provides case studies, homework problems, algorithms, and application examples. Drawing on years of robot-building and teaching experience, the author demonstrates how to build one example robot from beginning to end, with independent examples for extra modules.'--
Includes bibliographical references and index.
Keywords: Robots -- Design and construction; Robotics